Longitudinal Associations Between Cognition and Grip Strength, Differentiated by Sex and Physical Activity: A Population-Based Study in Older Adults from 17 European Countries - De Moraes-Ferrari, G (SAGE Publications Inc., 2025)
Objectives (1) To investigate longitudinal associations between grip strength (GS) and cognition over 4 years in European older adults, (2) to examine differences in temporal associations between men and women and between levels of physical activity, (3) to explore in each year 2015 and 2019 associations between GS quartiles and cognitive performance, and (4) to explore longitudinal associations between GS quartiles (year 2015) and cognitive performance (year 2019). Methods: 25,281 individuals (14,200 women) from 17 European countries aged ≥50 years responded to waves 6th and 8th of the SHARE project. We analyzed GS, a general cognition index, and physical activity level. Results: Panel analyses revealed a bidirectional relationship over 4 years between GS and cognition, with differences between sex, as well as between participants with moderate-to-vigorous and low physical activity levels. Conclusion: Women and participants with low physical activity were more likely to experience cognitive performance deficits 4 years later. © The Author(s) 2024